Behoort christene en marxiste in Suid - Afrika in dialoog met mekaar te tree? - Rossouw, G. J. (Koers, 1989)
Should Christians and Marxists enter into dialogue with each other? The question that is posed in this article is whether dialogue between Chr ist ians and Marxis ts in South Africa is desirable or not. Reasons are discussed for entering into a dialogue that was put forward by Christians and Marxists during the East European Christian -Marx is t dialogue, as well as those propagated b y the Christians for Socialism movement in Latin America. Each of these motivations for entering into dialogue is evaluated for its validity. Once the validity of some of these motivations has been proved, a description of the current state of attitudes towards a Chr istian-Marxis t dialogue in South Africa is given. The most popular objections against such a dialogue are discussed and it will be shown that these objections are unfounded. As an alternative approach to this negative attitude towards a dialogue a new approach will be propagated.